Pengetahuan Petani dalam Pemanfaatan Lahan Sawah Untuk Usahatani Semangka Desa Wolo Kecamatan Penawangan Kabupaten Grobogan - Sari, Irna Nur Fita; Hariyanto, Hariyanto (Edu Geography, 2019)
This study aims to (1) determine the knowledge of watermelon farmers in watermelon farming on Wolo the part of Penawangan District, Grobogan Regency, (2) Know th watermelon farmers income in watermelon farming on Wolo, Penawangan District, Grobogan Regency. The population of this study were farmers who cultivated watermelon on Wolo, Penawangan District, Grobogan District. The sample of this study were 40 technical watermelon farmers who were taken using total sampling technique. Data collection uses observation, documentation, questionnaires and interviews. Data analysis uses descriptive percentage analysis and revenue cost ratio. The results of the research show that the knowledge of watermelon farmers is in the medium category of 66.75%, even though the majority of formal education farmers only finish primary school. This is because farmers have experience of watermelon farming for more than 20 years which is indicates that the longer the farming experience is to form good knowledge. The income results of farmers grow watermelon as much as 2,69 times the capital issued. Penelitian ini bertujuan untuk (1) Mengetahui pengetahuan petani semangka dalam usahatani semangka di Desa Wolo Kecamatan Penawangan Kabupaten Grobogan, (2) Mengetahui Pendapatan petani semangka dalam usahatani semangka di Desa Wolo Kecamatan Penawangan Kabupaten Grobogan. Populasi penelitian ini adalah petani yang berusahatani semangka di Desa Wolo Kecamatan Penawangan Kabupaten Grobogan. Sampel penelitian ini sebanyak 40 petani semangka teknis yang diambil menggunakan teknik total sampling. Pengumpulan data menggunakan metode observasi, dokumetasi, angket dan wawancara. Analisis data menggunakan analisis deskriptif persentase dan revenue cost ratio. Hasil peneilitian menunjukkan pengetahuan petani semangka berada pada kategori sedang 66,75 %, walupun mayoritas pendidikan formal petani hanya tamat SD. Hal ini dikarenakan petani memiliki pengalaman berusahatani semangka lebih dari 20 tahun yang menandakan bahwa semakin lama pengalaman bertani maka membentuk pengetahuan yang baik. Hasil pendapatan petani menanam semangka sebanyak 2,69 kali modal yang dikeluarkan.